2023
DOI: 10.7717/peerj.14609
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of low-density lipoprotein cholesterol and all-cause or cardiovascular mortality in patients with type 2 diabetes: a retrospective study

Abstract: Background The optimal levels of low-density lipoprotein cholesterol (LDL-C) in patients with type 2 diabetes (T2D) are not currently clear. In this study, we determined the relationship between various mean LDL-C and all-cause or cardiovascular mortality risks in patients with T2D, stratifying by albumin level, age, sex, and antilipid medication use. We also evaluated the association of LDL-C standard deviation (LDL-C-SD) and all-cause and cardiovascular mortality by type of antilipid medicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Zhen Z et al reported there was a U-shaped relationship between untreated LDL-C level and all-cause mortality 34 and Tikhonoff V et al found LDL-C concentration is a multifaceted risk factor in older adults 35 . Chang C-H et al demonstrated both lower and higher levels of mean LDL-C were associated with increased all-cause and cardiovascular mortality in type 2 diabetes patients through 36 . Also, multiple studies in general population had got the similar result 17,[37][38][39] .…”
Section: Discussionmentioning
confidence: 99%
“…Zhen Z et al reported there was a U-shaped relationship between untreated LDL-C level and all-cause mortality 34 and Tikhonoff V et al found LDL-C concentration is a multifaceted risk factor in older adults 35 . Chang C-H et al demonstrated both lower and higher levels of mean LDL-C were associated with increased all-cause and cardiovascular mortality in type 2 diabetes patients through 36 . Also, multiple studies in general population had got the similar result 17,[37][38][39] .…”
Section: Discussionmentioning
confidence: 99%
“…A detailed definition of risk factors can be found in Additional file 1 : Table S2. We did not consider low-density lipoprotein (LDL) cholesterol as a risk factor because evident evidence has shown that low LDL cholesterol levels are associated with increased mortality risk in the general population and patients with T2D [ 10 , 20 22 ]. In a recent study of the UK Biobank, a significant U-shaped relationship was also observed between LDL cholesterol and all-cause mortality [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…FEMH, a tertiary medical center, has set up its electronic medical database of out-patient and emergency visits since 2001 and 2008, respectively. The details of our out-patient electronic database have been described in previous studies [12][13][14]. In this study, we extended our database to emergency visits electronic records.…”
Section: Study Subjectsmentioning
confidence: 99%
“…From the out-patient medical records, the information of oral hypoglycemic agents, insulin, antihypertensive and antilipid medications were collected during the study period as stated in our previous studies [12][13][14]. We also explored each study participant's comorbidities and complications as described in S1 Table [15].…”
Section: Follow-up Covariates and Study Endpointsmentioning
confidence: 99%